Evaluation of the level of corporate disclosure of listed companies in Singapore - Huang, Ming Hong (2009)
The disclosure level of financial information is crucial to parties involved both in preparing and using annual reports, especially to private investors. This is because a company's annual report is probably the single most important source of information available to private investors(SES survey, 1977). Within the annual report, financial statements provide the most comprehensive information thus are mostly used by the investors in their decision making.